Blackwood's Byron: The Lakers, the Cockneys, and the 'throne of poetical supremacy'. Issue 3 (October 2017) - Morrison, Robert
Abstract : Blackwood's in its earliest numbers was a staunch admirer of Lord Byron. But when he published Beppo, it damned him in a June 1818 review as a hypocrite and a reveller, and thereafter the magazine lurched between celebrating him for his genius and castigating him for his perversion of it. Byron objected to the uneven treatment he received at the hands of the Blackwood's critics, but in 'Some Observations Upon an Article in Blackwood's Edinburgh Magazine ' he echoes their views on several contemporary poets, and seems to reconcile himself to the exuberant unpredictability of the magazine.